الوعد والمواعدة في التبرعات والمعاوضات - Ben Mohamed, Abdallahi (International Islamic University Malaysia, 2010)

(untitled)
يتناول هذا البحث حكم كل من الوعد الصادر عن إرادة منفردة في باب التبرعات، والمواعدة الصادرة عن رغبة إرادتين في باب المعاوضات، من حيث لزوم الوفاء وعدمه في كل منهما ديانة وقضاء، وذلك من خلال استعراض آراء فقهاء المذاهب في لزوم الوفاء بالوعد أحادي الجانب فيما سبيله التبرع والإرفاق، واستعراض آراء المعاصرين من العلماء في إمكانية سحب الخلاف المذكور على ما استحدث اليوم من العقود القائمة على المواعدة في فيما سبيله المعاوضات والاسترباح، إضافة إلى محاولة التوصل إلى الرأي الراجح في المسألة ENGLISH : This study deals with the Islamic legal ruling of both promise which is made unilaterally in committing to give contribution on one hand, and contract which is made bilaterally in the cases of compensation giving. The Islamic legal ruling with respect to the commitment to fulfill or ignore them in the aspect of religious duty or law is dealt with. This is done through investigating the views of Islamic jurists on the obligation to fulfill the commitment made in unilateral promises, such as the promises in giving contribution and relief; and the views of contemporary jurists in order to assess the practicality of applying the divergent views which are adhered to by both parties on new situations which emerged today with respect to the promises and contracts in compensation giving and profit sharing –whether to oblige or neglect them. Ultimately, the most relevant view on the issue is concluded and presented.